Legal Problems of Cancellation of Deed of Sale and Purchase of Land Rights Due to One of the Parties Committing Default - Kholid, Muhammad Idham (Sultan Agung Notary Law Review, 2024)
This study aims to analyze: 1) Legal problems of land rights sale and purchase because one party is in default. 2). Legal protection for the injured party due to the cancellation of the land rights sale and purchase deed because one party is in default. This type of research is included in the scope of normative legal research. The approach method in this study is the statute approach. The type and source of data in this study are secondary data. obtained from literature studies. The analysis in this study is descriptive analytical. The results of the study concluded: 1). Legal problems of land rights sale and purchase because one party is in default, namely the party who feels aggrieved has the right to sue the Court to claim compensation, in the form of compensation for costs, losses and interest. Default causes legal certainty to be disturbed because the other party becomes uncertain about their rights and obligations. 2) Legal protection for the injured party due to the cancellation of the land rights sale and purchase deed because one party is in default, namely must include preventive and repressive measures. With preventive measures, such as making clear deeds and checking the legality of the land, as well as repressive measures, such as lawsuits and enforcement of sanctions, the legal system can provide comprehensive and effective protection for the injured party. This approach ensures that the law not only functions as a dispute resolution tool but also as a preventive mechanism that maintains justice and legal certainty in land sale and purchase transactions. However, legal protection does not apply to all buyers but only applies to certain buyer criteria. The criteria for buyers who are protected are those who have good intentions.